KINERJA KELOMPOK TANI PENGELOLA KEBUN BIBIT RAKYAT DI KABUPATEN BENGKULU SELATAN (STUDI KASUS KELOMPOK WANITA TANI USAHA BERSAMA DI DESA KOTA BUMI KECAMATAN PINO DAN KELOMPOK TANI BATU AMPAR JAYA DI DESA LUBUK TAPI KECAMATAN ULU MANNA) - Deselina, Deselina; Siswahyono, Siswahyono; Etrika, Gres Meik (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2014)
This study aims to determine the performance level of the farmer group manager of Community Seedling Garden (KBR) in South Bengkulu based indicators of the success of the planning, implementation, and monitoring and control and to determine the success of the planting is done farmer group KBR managers. The research was conducted in June – September 2013 in the Village of Kota Bumi District of Pino and the Village of Lubuk Tapi of Ulu Manna Sub Province of South Bengkulu). Respondent conducted census. Descriptive analysis of quantitative data is done to determine the level of performance and success of planting by KBR managers Group. Based of survey results revealed levels performance and success of the planting is done by the Woman Farmers Group Usaha Bersama is better than the results achieved by Farmers Group Batu Ampar Jaya.